2013
DOI: 10.1111/bor.12032
|View full text |Cite
|
Sign up to set email alerts
|

Asian monsoon climate during the Last Glacial Maximum: palaeo‐data–model comparisons

Abstract: The Last Glacial Maximum (LGM) (23-19 ka BP) in the Asian monsoon region is generally described as cool and dry, due to a strong winter monsoon. More recently, however, palaeo-data and climate model simulations have argued for a more variable LGM Asian monsoon climate with distinct regional differences. We compiled, evaluated, and partly re-assessed proxy records for the Asian monsoon region in terms of wet/dry climatic conditions based on precipitation and effective moisture, and of sea surface temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 144 publications
(281 reference statements)
7
23
0
Order By: Relevance
“…Six models have simulated the shifting except MRI-CGCM3. The shift of the Asian monsoon domain is consistent with the palaeo-data (Chabangborn et al 2014) and opposite to the simulated northward shift of the Asian summer monsoon circulation under CO 2 doubling (Kitoh et al 1997). Braconnot et al (2007b) also found that some of the models participated in PMIP2 simulated a southward shift of the intertropical convergence zone (ITCZ) over the continents and the Indian Ocean, which was in agreement with the results found from marine data (Leduc et al 2007).…”
Section: Global Monsoon Domain Changesupporting
confidence: 84%
See 1 more Smart Citation
“…Six models have simulated the shifting except MRI-CGCM3. The shift of the Asian monsoon domain is consistent with the palaeo-data (Chabangborn et al 2014) and opposite to the simulated northward shift of the Asian summer monsoon circulation under CO 2 doubling (Kitoh et al 1997). Braconnot et al (2007b) also found that some of the models participated in PMIP2 simulated a southward shift of the intertropical convergence zone (ITCZ) over the continents and the Indian Ocean, which was in agreement with the results found from marine data (Leduc et al 2007).…”
Section: Global Monsoon Domain Changesupporting
confidence: 84%
“…Proxy data revealed a stronger East Asian winter monsoon but weaker summer monsoon during glacial periods (Jiang and Lang 2010;Wang 2009). Chabangborn et al (2014) found that paleo-data and climate model simulation were agreed in a dry LGM climate in the western and northern part of the Asian monsoon region due to a stronger winter monsoon, and/or wetter conditions in equatorial areas of the Asian monsoon region due to a strengthened summer monsoon. However, the sparse reconstruction data in the global monsoon region make it difficult to pin down the uncertainty.…”
Section: Introductionmentioning
confidence: 88%
“…Significantly, based on a review of 75 time series datasets from monsoonal central Asia, Herzschuh (2006) argued that the LGM was characterized by dry or moderately dry climate conditions. Furthermore, modeling provides strong evidence for dry and cold climate conditions during the LGM period in the Asian monsoon region (Jiang and Lang, 2010;Jiang et al, 2011;Chabangborn et al, 2014).…”
Section: A Cool Dry Climate With Weaker Monsoons During the Lgmmentioning
confidence: 99%
“…In the past few decades, abrupt changes of the ISM have been inferred from marine sediments in the Arabian Sea (Schulz et al, 1998;Leuschner and Sirocko, 2000;Altabet et al, 2002;Govil and Naidu, 2010;Deplazes et al, 2013); the Bay of Bengal and the Andaman Sea (Colin et al, 1998) and speleothems from Socotra Island (Burns et al, 2003;Shakun et al, 2007), India (Sinha et al, 2005) and China (Cai et al, 2006). However, relatively few terrestrial paleoclimatic records of the ISM are from monsoon-dominated regions (Cook et al, 2013;Chabangborn et al, 2014;Dixit et al, 2014). In addition, the environmental significance of stable isotope records from stalagmites remains highly debated (Wang et al, 2001;Yuan et al, 2004;Maher, 2008;Clemens et al, 2010;Pausata et al, 2011;Liu et al, 2014;Tan, 2014).…”
Section: Introductionmentioning
confidence: 99%